Eye platelet-rich plasma in the treatment of ocular surface disorders. Issue 4 (July 2015) - Alio, Jorge L.; Rodriguez, Alejandra E.; WróbelDudzińska, Dominika
Abstract : Purpose of review: Blood-derived products [autologous serum, eye platelet-rich plasma (E-PRP), plasma rich in growth factors] are successful therapies for ocular surface disorders, which compromise the integrity of the cornea surface and conjunctiva. Recent findings: The most noteworthy and recent research has been directed towards hemoderivatives that include platelets. PRP for ophthalmologic use (E-PRP) has achieved successful outcomes as reported in the peer-review literature in the treatment of dry eye, post-laser in-situ keratomileusis ocular surface syndrome, dormant ulcers, and for ocular surface surgical reconstruction after corneal perforation associated to amniotic membrane transplantation, bovine pericardium membrane transplantation, or autologous fibrin membrane combined with solid PRP clot. Summary: PRP is a portion of the patient's own blood having a platelet concentration above baseline. The main advantage of PRP over other products is the presence of the platelets and associated with this the prolonged release of growth factors that are involved in the wound healing process of the cornea and conjunctival surface. E-PRP seems to be a reliable and effective therapeutic approach to enhance epithelial wound healing and promote ocular surface regeneration in different pathological conditions.